2011
DOI: 10.1002/jobm.201000384
|View full text |Cite
|
Sign up to set email alerts
|

Unusual occurrence of non carotenogenic strains of Dunaliella bardawil and Dunaliella parva in India

Abstract: Identification of green algal genus Dunaliella by conventional method is hard target since the strains vary morphologically and physiologically with conditions of growth. In this study, a total of nine different isolates of Dunaliella isolated from the salt pans of Tamil Nadu, India, were identified based on their morphology and cultural characteristics. In addition, the isolates were subjected to molecular identification using genus specific and species specific primers which distinguished the discrepancy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…All of them concluded that the intron-sizing method facilitated the precise identification of Dunaliella species that came from environmental samples. Additionally, other researchers combine molecular identification (intron-sizing method) with taxonomical characterization of Dunaliella species, achieving excellent results (Jayappriyan et al, 2011;Mishra et al, 2008;Preetha et al, 2012;Tempesta et al, 2011;Wang et al, 2014). Furthermore, research such as that by Dr. Hejazi and coworkers when using the intron-sizing method has served to identify new species of Dunaliella with a different intron arrangement (Hejazi et al, 2010).…”
Section: Identification Of Dunaliella Species From Certified Culture mentioning
confidence: 92%
See 1 more Smart Citation
“…All of them concluded that the intron-sizing method facilitated the precise identification of Dunaliella species that came from environmental samples. Additionally, other researchers combine molecular identification (intron-sizing method) with taxonomical characterization of Dunaliella species, achieving excellent results (Jayappriyan et al, 2011;Mishra et al, 2008;Preetha et al, 2012;Tempesta et al, 2011;Wang et al, 2014). Furthermore, research such as that by Dr. Hejazi and coworkers when using the intron-sizing method has served to identify new species of Dunaliella with a different intron arrangement (Hejazi et al, 2010).…”
Section: Identification Of Dunaliella Species From Certified Culture mentioning
confidence: 92%
“…The amount of b-carotene produced by these two species is practically the same (w10%), and also their taxonomic characteristics; however, the growth conditions and environmental parameters required for carotenoids production are quite different between both species (in preparation). In this sense, b-carotene production in D. bardawil is more difficult to induce than in D. salina, therefore some isolates of D. bardawil have been identified and classified as nonb-carotene producers (Jayappriyan et al, 2011). Microscopic analysis of D. salina 19/18 sample obtained from the Culture Collection of Algae and Protozoa (CCAP) showed two different strains of Dunaliella: one red and one green.…”
Section: Identification Of Dunaliella Species From Certified Culture mentioning
confidence: 99%
“…In 2011, Jayappriyan and coworkers [56] isolated several Dunaliella species samples from southern India where three species were identified: D. salina, D. parva, and D. bardawil. In this study the strains of D. parva and D. bardawil were reported as noncarotenogenic, possibly the culture conditions were not optimal to induce carotenogenesis.…”
Section: Dunaliellamentioning
confidence: 99%
“…In recent years, microalgae have been identified using morphological and molecular tools for their several purposes reported by many authors (Jayappriyan et al 2010(Jayappriyan et al , 2011. Worldwide, algae contain thousands of diverse strains.…”
Section: Integrated Palm Oil Mill Effluent Treatment and Biofuel Prodmentioning
confidence: 99%